Microscopic & macroscopic characterizations of Beijing marble as a building material for UNESCO heritage sites: New insights into physico-mechanical property estimation and weathering resistance. (20th November 2019) - Liu, Jian-bin; Zhang, Zhong-jian; Li, Biao
Highlights: Microscopic and macroscopic properties of Beijing marble are investigated. Statistical correlations among macroscopic parameters are studied. An on-site quality control method in selection of replacing pieces is proposed. Physico-mechanical properties of thirty-one types of marbles are compared. New insights into weathering mechanisms from perspective of multi-factor coupling. Abstract: Beijing marble has been used as a construction material for cultural heritage sites in Beijing area, China. The Forbidden City, the Temple of Heaven, the Summer Palace, and the Thirteen Ming Tombs are classified as UNESCO World Heritage sites. In this paper, detailed experimental and analytical investigations of two representative sub-types of Beijing marble are presented. Marble samples were collected from a historical quarry in Dashiwo County of Beijing's Fangshan District. Mineral and chemical constituents were investigated through petrographical observations, X-Ray Diffraction (XRD) analysis and X-Ray Fluorescence (XRF) analysis. Physical parameters (e.g., density, porosity, water absorption, pore size distribution, P-wave velocity (VP ), seismic anisotropy (AVP ), hardness, etc.) and mechanical parameters (i.e., uniaxial compressive strength (UCS) and Young's modulus (E)) were tested in accordance with British and Chinese standards. Correlations among tested parameters were also analyzed to better understand the internal relations among different properties and to aid in evaluating unattainable parameters during in-site heritage site assessments. To get a more comprehensive understanding of the marble's characteristics, we collected and analyzed those physico-mechanical data reported by previous researchers. Additionally, the weathering mechanisms and resistance of the marbles were discussed from different perspectives. The results of this study provide scientific data on the properties of Beijing dolomitic marble, which have practical use for weathering assessments and reconstruction of cultural heritage sites. Additionally, the results of this study provide a reliable reference for studying worldwide marbles with different geological origins.